Pengenalan Warna dan Gradasi pada Anak Usia Dini untuk Mengembangkan Kemampuan Mewarnai - Ratna Sari, Dewi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine how to recognize color and gradation in early childhood in RAMuslimat NU Ngluwar 2. These two abilities are very influential in developing children's abilities in the field of coloring. The study was conducted by observation, interview and documentation. The results showed: (1) In RA Muslimat NU Ngluwar 2 the recognition of colors and gradations is carried out through several stages including: preparation of materials, introduction of gradations and color combinations, coloring practices and block techniques. (2) Towards preparation for the race there are special treatments which include: more intense accompaniment, freedom to use gradations and emphasis on neatness